2012
DOI: 10.1002/ana.23805
|View full text |Cite
|
Sign up to set email alerts
|

Overinhibition of corticostriatal activity following prenatal cocaine exposure

Abstract: Objective-Prenatal cocaine exposure (PCE) can cause persistent neuropsychological and motor abnormalities in affected children, but the physiological consequences of PCE remain unclear. Conclusions drawn from clinical studies can sometimes be confounded by poly-substance abuse and nutritional deprivation. However, existing observations suggest that cocaine exposure in utero, as in adults, increases synaptic dopamine and promotes enduring dopamine-dependent plasticity at striatal synapses, altering behaviors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 50 publications
(167 reference statements)
0
24
0
Order By: Relevance
“…Accompanying this behavioral preference was increased volumes in the olfactory bulbs of the glomeruli that process cherry (M71-expressing olfactory sensory neurons and glomeruli) and mint (M72-expressing cells and glomeruli) (Todrank et al, 2011). In other studies, prenatal exposure to cocaine affected the F1 generation's behavior toward cocaine, as well as dopaminergic neurotransmission and stress responsiveness (Malanga et al, 2007;Wang et al, 2013). Additionally, exposure of pregnant rat dams to a fungicide, Vinclozolin, has been shown to affect reproductive and behavioral endpoints in several generations removed from this F0 exposure (Crews et al, 2007;Skinner et al, 2008;Gillette et al, 2014).…”
Section: Influence Of Environment In Utero On Biology Of Future Genermentioning
confidence: 94%
“…Accompanying this behavioral preference was increased volumes in the olfactory bulbs of the glomeruli that process cherry (M71-expressing olfactory sensory neurons and glomeruli) and mint (M72-expressing cells and glomeruli) (Todrank et al, 2011). In other studies, prenatal exposure to cocaine affected the F1 generation's behavior toward cocaine, as well as dopaminergic neurotransmission and stress responsiveness (Malanga et al, 2007;Wang et al, 2013). Additionally, exposure of pregnant rat dams to a fungicide, Vinclozolin, has been shown to affect reproductive and behavioral endpoints in several generations removed from this F0 exposure (Crews et al, 2007;Skinner et al, 2008;Gillette et al, 2014).…”
Section: Influence Of Environment In Utero On Biology Of Future Genermentioning
confidence: 94%
“…mEPSCs were recorded in gap-free mode both before and 10 min after beginning bath application of a receptor ligand (Wang et al, 2013). The Na ϩ channel antagonist TTX (1 M) was added to block spontaneous cortically derived action potentials and to isolate presynaptic terminal activity.…”
Section: Electrophysiologymentioning
confidence: 99%
“…9D-F ). The increase in firing frequency during withdrawal was dependent on dopamine release, because it was blocked (17 Ϯ 10%; 2.06 Ϯ 0.21 Hz in aCSF Wang et al, 2013). D, Representative traces from experimental results in E showing cell-attached recordings in saline-and amphetamine-treated TANs.…”
Section: Repeated Amphetamine Promotes Ppp In D1r-expressing Msns Thrmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical research has demonstrated significant effects of PCE on brain regions involved in emotional regulation, motivational control, and addiction vulnerability during adolescence (Chambers and Potenza, 2003)-eg, anterior cingulate (ACC) (Harvey, 2004), prefrontal cortex (PFC) (McCarthy and Bhide, 2012), and ventral striatum (VS) (Harvey et al, 2001;Wang et al, 2013). In humans, neurostructural (Rando et al, 2013) and neurofunctional (Li et al, 2009;Sheinkopf et al, 2009;Li et al, 2011) alterations (eg, during response inhibition, resting state alterations) in regions of the VS and PFC have also been reported among adolescents with PCE.…”
Section: Introductionmentioning
confidence: 99%